Atherogenic Index of Plasma mediates the association between Life’s Crucial 9 with overactive bladder: a secondary data analysis from NHANES - Gong, Hongyang; Lin, Xiaomei; Huang, Shaoqun (Frontiers in Endocrinology, 2025)
BackgroundSome studies suggest a potential link between cardiovascular health, lipid, and overactive bladder (OAB). Life’s Crucial 9 (LC9) is a recently developed method for assessing cardiovascular health, while the Atherogenic Index of Plasma (AIP) represents a novel marker of atherosclerotic lipid profiles. However, the relationship between Life’s Crucial 9 and overactive bladder and the role of Atherogenic Index of Plasma in the relationship between Life’s Crucial 9 and overactive bladder is unclear. This study investigates the relationship between Life’s Crucial 9 and overactive bladder and evaluates whether Atherogenic Index of Plasma influences this association.MethodsThis study conducted a cross-sectional analysis of 25,628 U.S. participants in the NHANES database from 2005-2018. Firstly, we used multivariate logistic regression to investigate the relationship between Life’s Crucial 9 and overactive bladder. Subsequently, subgroup analysis and restricted cubic splines (RCS) were further used to verify their relationship. Additionally, mediation analysis was conducted to explore the potential role of Atherogenic Index of Plasma levels in the association between Life’s Crucial 9 and overactive bladder.ResultsA total of 25,628 participants were included in this study, among whom 5,150 reported overactive bladder events. After using multivariate logistic regression to adjust for age, sex, race, marital status, education level, poverty-to-income ratio (PIR), smoking, alcohol consumption, hypertension, diabetes, and hypercholesterolemia, a 10-unit increase in Life’s Crucial 9 was associated with a 28% reduction in overactive bladder incidence (OR = 0.72, 95% CI: 0.69-0.76), while a 1-unit increase in Atherogenic Index of Plasma was associated with a 7% increase in overactive bladder incidence (OR = 1.07, 95% CI: 1.01-1.14). Similar results were obtained when Life’s Crucial 9 and Atherogenic Index of Plasma were categorized into tertiles, with a significant trend (P for trend < 0.05). Restricted cubic spline analysis revealed a linear negative correlation between Life’s Crucial 9 and overactive bladder incidence. Mediation analysis further indicated that 6.49% of the relationship between Life’s Crucial 9 and overactive bladder was mediated by Atherogenic Index of Plasma (P = 0.014).ConclusionThis study found a significant negative correlation between Life’s Crucial 9 and overactive bladder, with Atherogenic Index of Plasma partially mediating this relationship. These findings highlight the potential link between cardiovascular health and overactive bladder, underscoring the role of Life’s Crucial 9 in reducing overactive bladder incidence, possibly through its effects on lowering lipid levels.